Peningkatan Kesadaran Kesehatan Reproduksi Remaja melalui Edukasi Seksual yang Sehat di SMK Imelda Medan - Purba, Lamtiur; Harahap, Ali Asman; Gultom, Satriani H (Marsipature Hutanabe: Jurnal Pengabdian Kepada Masyarakat, 2025)
Adolescent reproductive health is an important aspect in the development of a healthy and quality young generation. Lack of knowledge about reproductive health can lead to risky behaviors among adolescents. This service aims to increase the awareness of students of Imelda Medan Private Vocational School about reproductive health through a healthy sexual education program. The methods used in this activity are lectures, interactive discussions, and case simulations. The results showed an increase in students' understanding of reproductive health, prevention of sexually transmitted diseases, and the importance of maintaining the health of the reproductive organs. Education provided systematically and based on scientific evidence has proven to be effective in increasing students' awareness of reproductive health